Identification of genome compositions in allopolyploid species of the genus Elymus(Poaceae: Triticeae) in the Asian part of Russia by CAPS analysis - A. V. Agafonov; E. V. Shabanova (Kobozeva); S. V. Asbaganov; A. V. Mglinets; V. S. Bogdanova (Вавиловский журнал генетики и селекции)
The genus ElymusL., together with wheat, rye, and barley, belongs to the tribe Triticeae. Apart from its  economic value, this tribe is characterized by abundance of polyploid taxa formed in the course of remote hybridization. Single-copy nuclear genes are convenient markers for identification of source genomes incorporated into  polyploids. In the present work, a CAPS-marker is developed to distinguish basic St, H, and Y genomes comprising  polyploid genomes of Asiatic species of the genus Elymus. The test is based on electrophoretic analysis of restriction patterns of a PCR-amplified fragment of the gene coding for beta-amylase. There are about 50 Elymusspecies  in Russia, and most of them are supposed to possess one of three haplome combinations, StH, StY and StHY. Boreal  StH-genomic species endemic for Russia are the least studied. On the basis of nucleotide sequences from public  databases, TaqI restrictase was selected, as it produced patterns of restriction fragments specific for St, H, and Y  haplomes easily recognizable in agarose gel. A sample of 68 accessions belonging to 32 species was analyzed.  In 15 species, the earlier known genomic constitutions were confirmed, but in E. kamojithis assay failed to reveal  the presence of H genome. This unusual H  genome was suggested to originate from a different Hordeum species. In 16 species, genomic constitutions were identified for the first time. Fifteen accessions from Asian Russia  possessed the genomic constitution StStHH, and E. amurensis, phylogenetically close to the StY-genomic species  E. ciliaris, had the genomic constitution StStYY. It is inferred that the center of species diversity of the StH-genomic  group is shifted to the north as compared to the center of origin of StY-genomic species, confined to China.